The International Environmental Law on the Eve of Reforms - M. N. Kopylov; A. M. Solntsev (Московский журнал международного права, 2010)
The current state of international legal regulation of international environmental relations, when rapidly augmenting normative array does not lead to real improvement of ecological situation in the world urgently calls for the need of serious reform of international environmental law, especially with regard to enhancing the effectiveness of existing mechanisms of environmental cooperation among states and the establishment of new mechanisms for such cooperation. In this paper the authors justify the need to establish a World environmental organization, to work out a unified international legal ecological act (World Environmental Constitution) and to found an International environmental court to solve urgent ecological issues.